A pretty tale of Ma and the maiden - Abd Razak, Dzulkifli (2006)
BY the time the muezzin called for maghrib prayers at the Masjid Kapitan Kling in Penang last weekend, the Gong Xi Fa Cai National Open House was about to wind down. As some Malaysians congregated at the mosque, the songs of celebration in conjunction with the open house were relayed over the nearby loudspeakers. Streams of people were mingling in front of the mosque as the chingay troupes skilfully showed off their artistic performances. Meanwhile, at the nearby "Little India" it was more than just business as usual. Nowhere else can these scenes be true except in Malaysia which is noted for its tolerance and richness as a confluence of many cultures.